Pengaruh Konservatisme Akuntansi dan Ukuran Perusahaan terhadap Peringkat Obligasi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Intan Trisnawati (Syntax Corporation Indonesia, 2023)
The purpose of this study was to test whether accounting conservatism and company size affect bond ratings in banking companies listed on the Indonesia Stock Exchange in 2017-2021. This type of research is quantitative research using secondary data. The sample in this study were banking companies listed on the Indonesia Stock Exchange and ranked by PT PEFINDO as many as 21 companies. Data collection techniques in this study are observation data, literature books, journals and articles. The data analysis used in this research is panel data regression analysis. The results of this study indicate that accounting conservatism has no effect while company size affects the bond rating of banking companies listed on the Indonesia Stock Exchange.